Answer:
[tex]x_1=1+\sqrt{89}\\\\x_2=1-\sqrt{89}[/tex]
Step-by-step explanation:
Apply Distributive property:
[tex](x+7)(x-9)=25\\\\x^2-9x+7x-63=25[/tex]
Add like terms and then add 63 to both sides of the equation:
[tex]x^2-2x-63=25\\\\x^2-2x-63+63=25+63\\\\x^2-2x=88[/tex]
Pick the coefficient of the x term, divide it by 2 and square it:
[tex](\frac{2}{2})^2=1[/tex]
Add it to both sides of the equation:
[tex]x^2-2x+1=88+1[/tex]
Rewriting the left side as a squared binomial, we get:
[tex](x-1)^2=89[/tex]
Apply square root to both sides:
[tex]\sqrt{(x-1)^2}=\±\sqrt{89}\\\\x-1=\±\sqrt{89}[/tex]
And finally we need to add 1 to both sides of the equation. Then we get:
[tex]x-1+1=\±\sqrt{89}+1\\\\x=\±\sqrt{89}+1\\\\\\x_1=1+\sqrt{89}\\\\x_2=1-\sqrt{89}[/tex]